2016
DOI: 10.1002/cncy.21789
|View full text |Cite
|
Sign up to set email alerts
|

Infections with multiple high‐risk HPV types are associated with high‐grade and persistent low‐grade intraepithelial lesions of the cervix

Abstract: High-risk mHPV infection identified patients with persistent LSIL/CIN1 and may to help identify patients at higher risk of disease progression to HSIL+/CIN2+. Longer follow-up will clarify the role of mHPV testing in patient care. Cancer Cytopathol 2017;125:138-143. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 19 publications
4
41
1
5
Order By: Relevance
“…This observation was corroborated by our findings in that a high viral load of HPV 16 was significantly different in LSIL compared to other groups [38]. Recent studies have shown a decrease in multiple HPV infections in HSIL cases compared to LSIL, unlike our study, where we found 55% multiple HPV infections in LSIL versus 62% in HSIL; in this Brazilian study, they found 58% multiple HPV infections in LSIL and 55% in HSIL cases [39]. Considering that our method is unable to detect LR-HPV, we cannot discard samples that might also have multiple HPV infections with an LR-HPV.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This observation was corroborated by our findings in that a high viral load of HPV 16 was significantly different in LSIL compared to other groups [38]. Recent studies have shown a decrease in multiple HPV infections in HSIL cases compared to LSIL, unlike our study, where we found 55% multiple HPV infections in LSIL versus 62% in HSIL; in this Brazilian study, they found 58% multiple HPV infections in LSIL and 55% in HSIL cases [39]. Considering that our method is unable to detect LR-HPV, we cannot discard samples that might also have multiple HPV infections with an LR-HPV.…”
Section: Discussionsupporting
confidence: 90%
“…This kit is based on simultaneous real-time amplification (multiplex PCR) of DNA fragments of 14 HR-HPV types (HPV 16,18,31,33,35,39,45,51,52,56,58,59, 66, and 68) and a DNA fragment of the ß-globin gene as an internal endogenous control, carried out in four separated reaction tubes. Each genotype is detected in a separate fluorescent channel (FAM, JOE, ROX, and Cy5) that allows its detection and quantification (a total of 16 qPCR probes are measured).…”
Section: Hpv Genotyping and Viral Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…When L1 gene methylation unchanged, it was 4.409 times to appear DNA heteroploid in multiple infection than single infection in Han women, in Uygur women, the OR was 3.279, the results accord with previous studies. [15,26] Compared to the Uygur women, HPV-16 infection status seemed to be more influence on Han women (OR: 3.297 vs 4.409). And L1 gene methylation created larger influence on Uygur women than Han women, in the same HPV infection, with a mild degree of L1 gene methylation as reference, Uygur women increase 5.075 and 63.634 times to appear DNA heteroploid when L1 gene methylation changed to moderate and severe grade, but the 2 OR values were 3.313 and 20.592 in Han women, which was smaller than Uygur women.…”
Section: Discussionmentioning
confidence: 99%
“…Graças às técnicas da biologia molecular, estabeleceu-se a relação entre a infecção persistente pelo HPV com alguns tipos virais e o câncer cervical e que infectam preferencialmente os órgãos genitais (vulva, vagina, colo uterino, pênis e áreas perianais) e orofaringe. Dessa forma, o HPV mesmo sendo reconhecido como fator de risco fundamental para câncer cervical não pode ser visto como a causa única para o desenvolvimento deste tipo de neoplasia maligna 13 .…”
Section: Revisão De Literaturaunclassified